PROSPECTS FOR INVESTMENT IN MINERAL RESOURCES SECTOR OF UKRAINE - Mykhailov, V.; Zagnitko, V.; Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers possibilities and conditions of attraction of investments into the domestic mineral resources base both for exploited deposits, to support and modernize existing fixed assets, and for deposits on the exploration and plant design stages. Currently mineral resources base comprises thousands of deposits with proven reserves that are exploited, and deposits that are potential investment targets. Mining and processing of mineral raw materials are asset-intensive industries, where construction and maintenance of expensive facilities, buying of mining and transport equipment are assumed. Investments in these sectors are typically large-scale projects with significant development terms, which is also associated with specific geological risk investments. The factors stated above define actuality of investment evaluation for domestic mineral resource base at various levels: local, individual mineral deposits, and regional and national ones to define the most strategic mineral materials. It is recommended to choose priority projects for investment in mineral resources after assessment of investment attractiveness, which involves of absolute and relative criteria determination and ranking of sites. Methods of assessment depends on investment objectives which are as follows: 1) assessment of feasibility of capital investments for expansion and technical reequipment of existing mining enterprises; 2) selection of alternative deposits for investments; 3) purchase of securities of individual mining companies. The list of evaluation criteria is defined for preliminary assessment of investment prospects in the domestic mineral complex. These criteria are based on qualitative and quantitative parameters of deposits, geological, mining, technological development conditions, and include main technical and economic indicators. Ranking of domestic mineral resources base objects is done for the major groups of fuel, metal and non-metallic minerals. Degree of investment attractiveness and level of investing risks in industrial development were used as main criteria.
Keywords: mineral resources; investment attraction; assessment of mineral deposits; exploration risks